Bank fraud exposed: with cases and preventive measures - Nwaze, Chuks (Lagos, Nigeria: Control and Surveillance Associates Ltd, 2006)
The book examines bank fraud in Nigeria and provides practical cases of and incidences of fraud. It also discusses anti-fraud mechanisms that range from diagnosis to preventive and preventive strategies.
Includes Index.
lje 04/09/2013
Loans
Keywords: Bank Fraud; Banks and Banking